Corporate Debt and Stock Returns : Evidence from U.S. Firms during the 2020 Oil Crash - Arezki, Rabah (World Bank, Washington, DC, 2022)
This paper explores the effect of oil price fluctuations on the stock returns of U.S. oil firms using an identification strategy through heteroskedasticity, exploiting the 2020 oil price crash. The results are twofold. First, a decline in oil prices significantly reduces oil firms’ stock returns. On average, a 1 percent decline in oil prices leads to a 0.44 percent decline in stock prices. Second, firm debt appears irrelevant in mediating the effect of oil prices on oil firms’ stock returns. Moreover, the muted role of debt was not likely caused by the liquidity backstop provided by the Federal Reserve.